Narratives at Work: Women, Men, Unionization, and the Fashioning of Identities - Webb, Jeff A. (Labour / Le Travail, 2004)
The article reviews the book, "Narratives at Work: Women, Men, Unionization, and the Fashioning of Identities, by Linda K. Cullum.

The Arthur Webb Story 1885-1964 - Webb, Jeff A. (Labour / Le Travail, 2001)
Written in the early 1960s and published for the first time in Labour/Le Travail, this memoir is of interest to labour historians for its portrayal of a working-class immigrant's life. The article introduces the autobiography of Arthur Webb, who in 1901 at age 16 emigrated from the UK to Canada. Webb reminisces about his childhood years in Liverpool (he began working at age 10 and had little formal education), then describes the series of temp jobs he held as a farm hand and labourer after his arrival in rural New Brunswick. He was a soldier before and during the First World War (he was gassed at Ypres) and latterly became a firefighter in Saskatoon, retiring in 1943 due to medical unfitness. He was deeply affected by the death of his wife in 1954, but remained determined to carry on - a recurring theme.

WCFL: Chicago's Voice of Labor, 1926-78 - Webb, Jeff A. (Labour / Le Travail, 1998)
The article reviews the book, "[Chicago Radio Station] WCFL: Chicago's Voice of Labor, 1926-78," by Nathan Godfried.